INVESTIGATION OF THE POLYETHYLENE GLYCOL AND CHERRY STEM WASTE RATIOS ON THE FINAL THERMAL, AND MECHANICAL PROPERTIES OF POLYVINYL ALCOHOL BASED COMPOSITE FILMS - Tuna, Sibel (My University, 2025)
“Green composites”, which are essentially composed of a biopolymer matrix and natural filler materials, have emerged as a significant alternative in the context of environmental pollution and sustainability studies in recent years. This study was designed to investigate the effects of polyethylene glycol (PEG) as a secondary polymer and cherry stem (CS) powder as a reinforcing phase on the thermal and mechanical performances of polyvinyl alcohol (PVA) based composite films. The composite films were produced using the solvent casting method. Taguchi optimization was performed to observe the effects of the PEG and CS ratios. The properties of the composite films were evaluated using Fourier transform infrared spectroscopy, thermogravimetric analysis, and mechanical testing. It was determined that the use of PEG improves the thermal properties due to its high thermal stability, as well as improving the elongation at break values, while decreasing tensile strength due to its plasticizing effect. CS generally improves thermal properties and tensile strength by up to 5% but decreases by 10% due to agglomeration. Elongation at break decreases as the amount of CS increases.
Keywords: Taguchi optimization; Polymeric Film Composites; Biobased polymeric composites; Natural based fillers.